High-capacity high-safety low-temperature lithium battery and preparation method thereof

By using composite lithium iron phosphate positive electrode material and hard carbon negative electrode material, the freezing resistance and stability of low-temperature lithium batteries in cold environments is solved, and higher application and stability are achieved.

CN119419374AInactive Publication Date: 2025-02-11NANTONG BAIXING POWER EQUIP CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411530988.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing low-temperature lithium batteries have poor application and stability in cold environments and are not very freezing resistance.

Method used

The composite lithium iron phosphate positive electrode material and hard carbon negative electrode material are used to mix dryly through silicone coupling agent to increase the layer spacing of the material, and the slurry viscosity is adjusted by adding solvents to ensure uniform coating and high density of the electrode material. .

Benefits of technology

It significantly improves the freezing rate and stability of low-temperature lithium batteries, and improves the applicability and stability of use in cold environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419374A_ABST
    Figure CN119419374A_ABST
Patent Text Reader

Abstract

The invention discloses a high-capacity and high-safety low-temperature lithium battery and a preparation method thereof, and relates to the technical field of low-temperature lithium batteries, a positive electrode material comprises the following components in parts by weight: 2-40 parts of graphene, 2-40 parts of carbon nanotubes and 200-300 parts of nano lithium iron phosphate, the material A is uniformly mixed by a dry method through an organic silicon coupling agent, and a mixture is obtained; the composite lithium iron phosphate positive electrode material comprises, by mass, 0.1%-5% of graphene, 0.1%-5% of carbon nanotubes and 96%-99% of nanometer lithium iron phosphate, primary particles of the nanometer lithium iron phosphate are 50140nm nanoscale glume particles, and secondary particles of the nanometer lithium iron phosphate are 50140nm nanoscale glume particles. The preparation method comprises the following steps: adding 80-110 parts by weight of binder polyvinylidene fluoride, 8-15 parts by weight of conductive agent SP and 4-15 parts by weight of solvent NMP into a composite lithium iron phosphate positive electrode material, uniformly stirring to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of the composite lithium iron phosphate positive electrode material, the conductive agent SP and the binder polyvinylidene fluoride PVDF is (95-100): (2-3): (1-4), and adjusting the viscosity of the slurry by adding the solvent NMP.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of low-temperature lithium batteries, and in particular to a low-temperature lithium battery with large capacity and high safety and a preparation method thereof. Background Art

[0002] Low-temperature lithium batteries were originally used in the aerospace field to provide power for spacecraft and satellites. With the popularity of electric vehicles and portable devices, people's demand for high-performance low-temperature lithium batteries has gradually increased. Researchers are committed to improving the structure and materials of low-temperature lithium batteries to improve their performance and stability. The safety performance of lithium batteries in low-temperature environments is also an urgent problem to be solved. Low-temperature lithium batteries can effectively improve their explosion-proof properties by adopting more stable materials and structures. However, the existing low-temperature lithium batteries have low frost resistance and poor applicability and stability in cold environments.

[0003] The defects of existing low-temperature lithium batteries are:

[0004] 1. Patent document CN111816882B discloses a low-temperature electrode sheet, a preparation method thereof and a low-temperature lithium battery. "The low-temperature electrode sheet includes an electrode material and a current collector with a chelating coating on the surface; the current collector with a chelating coating on the surface includes: a current collector and a chelating conversion coating on the surface of the current collector; wherein the chelating conversion coating has P=O and P-OH bonds and has a SiO2 nanolayer structure; the chelating conversion coating is obtained by: dissolving vinyl silane in a mixed solution of ethanol and acetone to form a first solution, dissolving phytic acid in a Tris-HCL buffer to form a second solution, and adding the first solution to the second solution to generate a chelating reaction", but the existing low-temperature lithium battery has low frost resistance and poor applicability and stability in cold environments;

[0005] 2. Patent document CN109802094A discloses a low-temperature lithium iron phosphate battery, "including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet is made by coating a positive electrode slurry including a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and a positive electrode solvent onto a positive electrode current collector; the positive electrode active material is Ti3SiC2-modified carbon-coated lithium iron phosphate; the positive electrode conductive agent is carbon nanotubes and graphene; the negative electrode sheet is made of a negative electrode active material, a negative electrode conductive agent, a negative electrode binder, a thickener and The negative electrode slurry of the negative electrode solvent is coated on the negative electrode current collector; the negative electrode active material is artificial graphite and mesophase carbon microspheres; the negative electrode conductive agent is carbon nanotubes and graphene. The experimental results show that the discharge capacity of the battery of the present invention at -20°C is 2488mAh, which is 88.13% of the room temperature capacity; the discharge capacity at -40°C is 2215mAh, which is 78.46% of the room temperature discharge capacity. However, the existing low-temperature lithium battery has low frost resistance and poor applicability and stability in cold environments.

[0006] 3. Patent document CN109119699A discloses a low-temperature improved lithium titanate battery and its preparation method. "The method includes preparing a conductive agent-containing glue solution, preparing a positive electrode slurry, preparing a negative electrode slurry, preparing a positive electrode sheet, preparing a negative electrode sheet and battery assembly, wherein the preparation of the conductive agent-containing glue solution includes mixing a binder, a first solvent and a conductive agent; the preparation of the positive electrode slurry includes mixing a positive electrode material with a conductive agent-containing glue solution; the preparation of the negative electrode slurry includes mixing a negative electrode material with a conductive agent-containing glue solution; the preparation of the positive electrode sheet includes coating the positive electrode slurry on a current collector and baking it, and the preparation of the negative electrode sheet includes coating the negative electrode slurry on a current collector and baking it; the battery assembly includes loading the positive electrode sheet and the negative electrode sheet into a housing, injecting an electrolyte and packaging it; the lithium titanate battery prepared by the above method has a higher energy density and better discharge performance in a low temperature environment", but the existing low-temperature lithium battery has low frost resistance and poor applicability and stability in a cold environment;

[0007] 4. Patent document CN113594544B discloses an electrolyte for low-temperature lithium batteries and a preparation method thereof. "The electrolyte comprises a lithium salt, an organic solvent and a low-temperature additive, wherein the low-temperature additive is a mixture of potassium bromide, phenylcyclohexane, succinonitrile and fluoroethylene carbonate, and the mass content of the low-temperature additive in the electrolyte is 0.08-0.15%; compared with the prior art, in the technical solution provided by the present invention, a multi-component mixed low-temperature additive is added to the electrolyte, thereby improving the state of the electrolyte at low temperatures and the composition of the SEI film in multiple aspects, thereby significantly improving the capacity and cycle life of the lithium battery at low temperatures." However, the existing low-temperature lithium batteries have low frost resistance and poor applicability and stability for use in cold environments. Summary of the invention

[0008] The purpose of the present invention is to provide a large-capacity, high-safety low-temperature lithium battery and a preparation method thereof, so as to solve the technical problems raised in the above background technology that the existing low-temperature lithium batteries have low frost resistance, poor applicability and stability in cold environments.

[0009] To achieve the above object, the present invention provides the following technical solution: a method for preparing a low-temperature lithium battery with large capacity and high safety, comprising the following steps;

[0010] Step S1, preparing positive electrode material;

[0011] Step S2, preparing negative electrode materials;

[0012] Step S3, preparation of pole piece;

[0013] Step S4, assembling the cells into lithium batteries;

[0014] The positive electrode material comprises the following parts by weight of material A, 2-40 parts of graphene, 2-40 parts of carbon nanotubes, and 200-300 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1%-5%, 0.1%-5%, and 96%-99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following parts by weight of binder polyvinylidene fluoride are added to the composite lithium iron phosphate positive electrode material: 80-110 parts, 8-15 parts of conductive agent SP, 4-15 parts of solvent NMP, stirring to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of composite lithium iron phosphate positive electrode material, conductive agent SP, and binder polyvinylidene fluoride PVDF is 95-100:2-3:1-4, and the viscosity of the slurry is adjusted by adding solvent NMP to make the viscosity of the lithium iron phosphate positive electrode material slurry reach 8050-15050mPa.s, the solid content is 50%, and the lithium iron phosphate positive electrode material slurry is coated after sieving, and the double-sided coating surface density of the positive electrode sheet is 150-300g / cm 2 , one of the elements Mn, Al, Cr, Mg, and F is added to the positive electrode material slurry to perform bulk doping on the positive electrode material and increase the interlayer spacing of the material.

[0015] Preferably, the negative electrode material includes the following parts by weight of hard carbon negative electrode material 15-40 parts, sodium carboxymethyl cellulose 20-60 parts, styrene-butadiene rubber 25-45 parts, and water 40-60 parts, which are evenly mixed to form material B. The porosity of the hard carbon negative electrode material is 3%-10%, and the mass ratio of the hard carbon material, sodium carboxymethyl cellulose, and styrene-butadiene rubber is 96-125:2-5:2-5. Material B is glued into a negative electrode slurry, and the solid content of the negative electrode slurry is 55-60%. The negative electrode slurry is coated, and the double-sided coating surface density of the negative electrode plate is 60-120 g / cm2. One of the elements B and K is introduced into the negative electrode slurry to improve the graphite structure and increase the interlayer spacing.

[0016] Preferably, the CA ratio of the negative electrode sheet to the positive electrode sheet is 1.05-1.20, the coated positive electrode sheet and negative electrode sheet are dried, rolled, cut, and the tabs are welded, and both the positive and negative electrode tabs are full tabs.

[0017] Preferably, 10 to 15 parts by weight of N-methylpyrrolidone is added to the positive electrode material slurry, and the mixture is stirred to form a uniform positive electrode material slurry.

[0018] Preferably, 12 to 18 parts by weight of styrene-butadiene rubber is added to the negative electrode slurry. Styrene-butadiene rubber can improve the stability and safety of the negative electrode structure.

[0019] Preferably, a separator is provided between the positive electrode plate and the negative electrode plate, and the separator is one of polyethylene and polypropylene.

[0020] Preferably, the positive electrode sheet, the negative electrode sheet and the separator are wound to form a battery cell, the battery cell is placed in a shell and injected with electrolyte, the battery cell is sealed, and chemical processing is performed to obtain a low-temperature lithium battery.

[0021] Preferably, it comprises the shell, the battery core and the electrolyte, the battery core is installed on the inner wall of the shell, and the electrolyte is filled on the inner wall of the shell.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention is provided with a positive electrode material including the following weight parts of material A, 26 parts of graphene, 32 parts of carbon nanotubes, and 290 parts of nano lithium iron phosphate, and material A is dry mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material, wherein the mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively, and the primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm, and the composite lithium iron phosphate positive electrode material is added Add the following weight parts of binder polyvinylidene fluoride 112 parts, conductive agent SP 14 parts, solvent NMP 12 parts, stir to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of composite lithium iron phosphate positive electrode material, conductive agent SP, binder polyvinylidene fluoride PVDF is 95-100: 2-3: 1-4, and the viscosity of the slurry is adjusted by adding solvent NMP, so that the viscosity of the lithium iron phosphate positive electrode material slurry reaches 8050-15050 mPa.s, thereby achieving the significant improvement of the freezing resistance of the low-temperature lithium battery of the present invention and improving the applicability of use in cold environments;

[0024] 2. The present invention realizes bulk doping of the positive electrode material by adding one of the elements Mn, Al, Cr, Mg, and F into the positive electrode material slurry to increase the interlayer spacing of the material. The negative electrode material comprises the following parts by weight of hard carbon negative electrode material 15 to 40 parts, sodium carboxymethyl cellulose 20 to 60 parts, styrene-butadiene rubber 25 to 45 parts, and water 40 to 60 parts, which are evenly mixed to form material B. The porosity of the hard carbon negative electrode material is 3% to 10%. The mass ratio of the hard carbon material, sodium carboxymethyl cellulose, and styrene-butadiene rubber is 96 to 125:2 to 5:2 to 5. Material B is glued into a negative electrode slurry with a solid content of 55 to 60%. The negative electrode slurry is coated, thereby significantly improving the stability of the low-temperature lithium battery of the present invention and improving the stability of use in cold environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a front view structural schematic diagram of the present invention;

[0026] Figure 2 It is a front structural schematic diagram of the present invention;

[0027] Figure 3 It is a schematic diagram of experimental data of the present invention.

[0028] In the figure: 1. shell; 2. battery cell; 3. electrolyte. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front end", "rear end", "two ends", "one end", "the other end" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0031] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "provided with", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, it can be understood according to the specific situation.

[0032] Example 1: Please refer to Figure 1 , Figure 2 and Figure 3 , an embodiment provided by the present invention: a method for preparing a low-temperature lithium battery with large capacity and high safety, comprising the following steps;

[0033] Step S1, preparing positive electrode material;

[0034] Step S2, preparing negative electrode materials;

[0035] Step S3, preparation of pole piece;

[0036] Step S4, assembling the battery cells 2 into a lithium battery;

[0037] The positive electrode material includes the following weight parts of material A, 5 parts of graphene, 5 parts of carbon nanotubes, and 220 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following weight parts of binder polyvinylidene fluoride are added to the composite lithium iron phosphate positive electrode material: 0 parts, 10 parts of conductive agent SP, 6 parts of solvent NMP, stirring to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of composite lithium iron phosphate positive electrode material, conductive agent SP, and binder polyvinylidene fluoride PVDF is 95-100: 2-3: 1-4, and the viscosity of the slurry is adjusted by adding solvent NMP to make the viscosity of the lithium iron phosphate positive electrode material slurry reach 8050-15050mPa.s, the solid content is 50%, and the slurry is coated after sieving, and the lithium iron phosphate positive electrode material slurry and are coated, and the double-sided coating surface density of the positive electrode sheet is 150-300g / cm 2 , one of the elements Mn, Al, Cr, Mg, and F is added to the positive electrode material slurry to perform bulk doping on the positive electrode material to increase the interlayer spacing of the material. The negative electrode material includes the following parts by weight of hard carbon negative electrode material 15 to 40 parts, sodium carboxymethyl cellulose 20 to 60 parts, styrene butadiene rubber 25 to 45 parts, and water 40 to 60 parts, which are mixed evenly to form material B. The porosity of the hard carbon negative electrode material is 3% to 10%. The mass ratio of hard carbon material, sodium carboxymethyl cellulose, and styrene butadiene rubber is 96 to 125:2 to 5:2 to 5. Material B is glued into a negative electrode slurry, and the solid content of the negative electrode slurry is 55 to 60%. The negative electrode slurry is coated, and the double-sided coating surface density of the negative electrode sheet is 60 to 120 g / cm2. One of the elements B and K is introduced into the negative electrode slurry to improve the graphite structure and increase the interlayer spacing. The CA ratio of the negative electrode sheet to the positive electrode sheet is The positive electrode sheet and the negative electrode sheet are dried, rolled, cut, and the pole ears are welded. The positive and negative pole ears are full pole ears. 10 to 15 parts by weight of N-methylpyrrolidone are added to the positive electrode material slurry, and a uniform positive electrode material slurry is formed after stirring. 12 to 18 parts by weight of styrene-butadiene rubber are added to the negative electrode slurry. The styrene-butadiene rubber can improve the stability and safety of the negative electrode structure. A diaphragm is provided between the positive electrode sheet and the negative electrode sheet. The diaphragm is one of polyethylene and polypropylene. The positive electrode sheet, the negative electrode sheet and the diaphragm are wound to form a battery cell 2. The battery cell 2 is placed in the shell 1 and the electrolyte 3 is injected. The battery cell 2 is sealed and subjected to a chemical composition treatment to obtain a low-temperature lithium battery, including a shell 1, a battery cell 2, and an electrolyte 3. The inner wall of the shell 1 is provided with a battery cell 2, and the inner wall of the shell 1 is filled with the electrolyte 3.

[0038] Example 2: Please refer to Figure 1 , Figure 2 and Figure 3 , an embodiment provided by the present invention: a method for preparing a low-temperature lithium battery with large capacity and high safety, comprising the following steps;

[0039] Step S1, preparing positive electrode material;

[0040] Step S2, preparing negative electrode materials;

[0041] Step S3, preparation of pole piece;

[0042] Step S4, assembling the battery cells 2 into a lithium battery;

[0043] The positive electrode material includes the following weight parts of material A, 10 parts of graphene, 10 parts of carbon nanotubes, and 280 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following weight parts of binder polyvinylidene fluoride are added to the composite lithium iron phosphate positive electrode material: 00 parts, 12 parts of conductive agent SP, 6 parts of solvent NMP, stir to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of composite lithium iron phosphate positive electrode material, conductive agent SP, and binder polyvinylidene fluoride PVDF is 95-100: 2-3: 1-4, and the viscosity of the slurry is adjusted by adding solvent NMP to make the viscosity of the lithium iron phosphate positive electrode material slurry reach 8050-15050mPa.s, the solid content is 50%, and the slurry is sieved and coated. The lithium iron phosphate positive electrode material slurry and the positive electrode sheet are coated, and the double-sided coating surface density is 150-300g / cm 2, one of the elements Mn, Al, Cr, Mg, and F is added to the positive electrode material slurry to perform bulk doping on the positive electrode material to increase the interlayer spacing of the material. The negative electrode material includes the following parts by weight of hard carbon negative electrode material 15 to 40 parts, sodium carboxymethyl cellulose 20 to 60 parts, styrene butadiene rubber 25 to 45 parts, and water 40 to 60 parts, which are mixed evenly to form material B. The porosity of the hard carbon negative electrode material is 3% to 10%. The mass ratio of hard carbon material, sodium carboxymethyl cellulose, and styrene butadiene rubber is 96 to 125:2 to 5:2 to 5. Material B is glued into a negative electrode slurry, and the solid content of the negative electrode slurry is 55 to 60%. The negative electrode slurry is coated, and the double-sided coating surface density of the negative electrode sheet is 60 to 120 g / cm2. One of the elements B and K is introduced into the negative electrode slurry to improve the graphite structure and increase the interlayer spacing. The CA ratio of the negative electrode sheet to the positive electrode sheet is The positive electrode sheet and the negative electrode sheet are dried, rolled, cut, and the pole ears are welded. The positive and negative pole ears are full pole ears. 10 to 15 parts by weight of N-methylpyrrolidone are added to the positive electrode material slurry, and a uniform positive electrode material slurry is formed after stirring. 12 to 18 parts by weight of styrene-butadiene rubber are added to the negative electrode slurry. The styrene-butadiene rubber can improve the stability and safety of the negative electrode structure. A diaphragm is provided between the positive electrode sheet and the negative electrode sheet. The diaphragm is one of polyethylene and polypropylene. The positive electrode sheet, the negative electrode sheet and the diaphragm are wound to form a battery cell 2. The battery cell 2 is placed in the shell 1 and the electrolyte 3 is injected. The battery cell 2 is sealed and subjected to a chemical composition treatment to obtain a low-temperature lithium battery, including a shell 1, a battery cell 2, and an electrolyte 3. The inner wall of the shell 1 is provided with a battery cell 2, and the inner wall of the shell 1 is filled with the electrolyte 3.

[0044] Example 3: Please refer to Figure 1 , Figure 2 and Figure 3 , an embodiment provided by the present invention: a method for preparing a low-temperature lithium battery with large capacity and high safety, comprising the following steps;

[0045] Step S1, preparing positive electrode material;

[0046] Step S2, preparing negative electrode materials;

[0047] Step S3, preparation of pole piece;

[0048] Step S4, assembling the battery cells 2 into a lithium battery;

[0049] The positive electrode material includes the following weight parts of material A, 25 parts of graphene, 15 parts of carbon nanotubes, and 250 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following weight parts of binder polyvinylidene fluoride are added to the composite lithium iron phosphate positive electrode material: 15 parts, 13 parts of conductive agent SP, 7 parts of solvent NMP, stir to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of composite lithium iron phosphate positive electrode material, conductive agent SP, and binder polyvinylidene fluoride PVDF is 95-100: 2-3: 1-4, and the viscosity of the slurry is adjusted by adding solvent NMP to make the viscosity of the lithium iron phosphate positive electrode material slurry reach 8050-15050mPa.s, the solid content is 50%, and the slurry is coated after sieving. The lithium iron phosphate positive electrode material slurry and the positive electrode sheet are coated, and the double-sided coating surface density is 150-300g / cm 2 , one of the elements Mn, Al, Cr, Mg, and F is added to the positive electrode material slurry to perform bulk doping on the positive electrode material to increase the interlayer spacing of the material. The negative electrode material includes the following parts by weight of hard carbon negative electrode material 15 to 40 parts, sodium carboxymethyl cellulose 20 to 60 parts, styrene butadiene rubber 25 to 45 parts, and water 40 to 60 parts, which are mixed evenly to form material B. The porosity of the hard carbon negative electrode material is 3% to 10%. The mass ratio of hard carbon material, sodium carboxymethyl cellulose, and styrene butadiene rubber is 96 to 125:2 to 5:2 to 5. Material B is glued into a negative electrode slurry, and the solid content of the negative electrode slurry is 55 to 60%. The negative electrode slurry is coated, and the double-sided coating surface density of the negative electrode sheet is 60 to 120 g / cm2. One of the elements B and K is introduced into the negative electrode slurry to improve the graphite structure and increase the interlayer spacing. The CA ratio of the negative electrode sheet to the positive electrode sheet is The positive electrode sheet and the negative electrode sheet are dried, rolled, cut, and the pole ears are welded. The positive and negative pole ears are full pole ears. 10 to 15 parts by weight of N-methylpyrrolidone are added to the positive electrode material slurry, and a uniform positive electrode material slurry is formed after stirring. 12 to 18 parts by weight of styrene-butadiene rubber are added to the negative electrode slurry. The styrene-butadiene rubber can improve the stability and safety of the negative electrode structure. A diaphragm is provided between the positive electrode sheet and the negative electrode sheet. The diaphragm is one of polyethylene and polypropylene. The positive electrode sheet, the negative electrode sheet and the diaphragm are wound to form a battery cell 2. The battery cell 2 is placed in the shell 1 and the electrolyte 3 is injected. The battery cell 2 is sealed and subjected to a chemical composition treatment to obtain a low-temperature lithium battery, including a shell 1, a battery cell 2, and an electrolyte 3. The inner wall of the shell 1 is provided with a battery cell 2, and the inner wall of the shell 1 is filled with the electrolyte 3.

[0050] Example 4: Please refer to Figure 1 , Figure 2 and Figure 3 , an embodiment provided by the present invention: a method for preparing a low-temperature lithium battery with large capacity and high safety, comprising the following steps;

[0051] Step S1, preparing positive electrode material;

[0052] Step S2, preparing negative electrode materials;

[0053] Step S3, preparation of pole piece;

[0054] Step S4, assembling the battery cells 2 into a lithium battery;

[0055] The positive electrode material includes the following weight parts of material A, 35 parts of graphene, 25 parts of carbon nanotubes, and 290 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following weight parts of binder polyvinylidene fluoride are added to the composite lithium iron phosphate positive electrode material: 90 parts, 13 parts of conductive agent SP, 8 parts of solvent NMP, stir to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of composite lithium iron phosphate positive electrode material, conductive agent SP, and binder polyvinylidene fluoride PVDF is 95-100: 2-3: 1-4, and the viscosity of the slurry is adjusted by adding solvent NMP to make the viscosity of the lithium iron phosphate positive electrode material slurry reach 8050-15050mPa.s, the solid content is 50%, and the lithium iron phosphate positive electrode material slurry is coated after sieving, and the double-sided coating surface density of the positive electrode sheet is 150-300g / cm 2, one of the elements Mn, Al, Cr, Mg, and F is added to the positive electrode material slurry to perform bulk doping on the positive electrode material to increase the interlayer spacing of the material. The negative electrode material includes the following parts by weight of hard carbon negative electrode material 15 to 40 parts, sodium carboxymethyl cellulose 20 to 60 parts, styrene butadiene rubber 25 to 45 parts, and water 40 to 60 parts, which are mixed evenly to form material B. The porosity of the hard carbon negative electrode material is 3% to 10%. The mass ratio of hard carbon material, sodium carboxymethyl cellulose, and styrene butadiene rubber is 96 to 125:2 to 5:2 to 5. Material B is glued into a negative electrode slurry, and the solid content of the negative electrode slurry is 55 to 60%. The negative electrode slurry is coated, and the double-sided coating surface density of the negative electrode sheet is 60 to 120 g / cm2. One of the elements B and K is introduced into the negative electrode slurry to improve the graphite structure and increase the interlayer spacing. The CA ratio of the negative electrode sheet to the positive electrode sheet is The positive electrode sheet and the negative electrode sheet are dried, rolled, cut, and the pole ears are welded. The positive and negative pole ears are full pole ears. 10 to 15 parts by weight of N-methylpyrrolidone are added to the positive electrode material slurry, and a uniform positive electrode material slurry is formed after stirring. 12 to 18 parts by weight of styrene-butadiene rubber are added to the negative electrode slurry. The styrene-butadiene rubber can improve the stability and safety of the negative electrode structure. A diaphragm is provided between the positive electrode sheet and the negative electrode sheet. The diaphragm is one of polyethylene and polypropylene. The positive electrode sheet, the negative electrode sheet and the diaphragm are wound to form a battery cell 2. The battery cell 2 is placed in the shell 1 and the electrolyte 3 is injected. The battery cell 2 is sealed and subjected to a chemical composition treatment to obtain a low-temperature lithium battery, including a shell 1, a battery cell 2, and an electrolyte 3. The inner wall of the shell 1 is provided with a battery cell 2, and the inner wall of the shell 1 is filled with the electrolyte 3.

[0056] Example 5: Please refer to Figure 1 , Figure 2 and Figure 3 , an embodiment provided by the present invention: a method for preparing a low-temperature lithium battery with large capacity and high safety, comprising the following steps;

[0057] Step S1, preparing positive electrode material;

[0058] Step S2, preparing negative electrode materials;

[0059] Step S3, preparation of pole piece;

[0060] Step S4, assembling the battery cells 2 into a lithium battery;

[0061] The positive electrode material includes the following parts by weight of material A, 26 parts of graphene, 32 parts of carbon nanotubes, and 290 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following parts by weight of a binder polyvinylidene fluoride are added to the composite lithium iron phosphate positive electrode material: 12 parts, 14 parts of conductive agent SP, 12 parts of solvent NMP, stir to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of composite lithium iron phosphate positive electrode material, conductive agent SP, and binder polyvinylidene fluoride PVDF is 95-100: 2-3: 1-4, and the viscosity of the slurry is adjusted by adding solvent NMP to make the viscosity of the lithium iron phosphate positive electrode material slurry reach 8050-15050mPa.s, the solid content is 50%, and the slurry is sieved and coated. The lithium iron phosphate positive electrode material slurry and the positive electrode sheet are coated, and the double-sided coating surface density is 150-300g / cm 2 , one of the elements Mn, Al, Cr, Mg, and F is added to the positive electrode material slurry to perform bulk doping on the positive electrode material to increase the interlayer spacing of the material. The negative electrode material includes the following parts by weight of hard carbon negative electrode material 15 to 40 parts, sodium carboxymethyl cellulose 20 to 60 parts, styrene butadiene rubber 25 to 45 parts, and water 40 to 60 parts, which are mixed evenly to form material B. The porosity of the hard carbon negative electrode material is 3% to 10%. The mass ratio of hard carbon material, sodium carboxymethyl cellulose, and styrene butadiene rubber is 96 to 125:2 to 5:2 to 5. Material B is glued into a negative electrode slurry, and the solid content of the negative electrode slurry is 55 to 60%. The negative electrode slurry is coated, and the double-sided coating surface density of the negative electrode sheet is 60 to 120 g / cm2. One of the elements B and K is introduced into the negative electrode slurry to improve the graphite structure and increase the interlayer spacing. The CA ratio of the negative electrode sheet to the positive electrode sheet is The positive electrode sheet and the negative electrode sheet are dried, rolled, cut, and the pole ears are welded. The positive and negative pole ears are full pole ears. 10 to 15 parts by weight of N-methylpyrrolidone are added to the positive electrode material slurry, and a uniform positive electrode material slurry is formed after stirring. 12 to 18 parts by weight of styrene-butadiene rubber are added to the negative electrode slurry. The styrene-butadiene rubber can improve the stability and safety of the negative electrode structure. A diaphragm is provided between the positive electrode sheet and the negative electrode sheet. The diaphragm is one of polyethylene and polypropylene. The positive electrode sheet, the negative electrode sheet and the diaphragm are wound to form a battery cell 2. The battery cell 2 is placed in the shell 1 and the electrolyte 3 is injected. The battery cell 2 is sealed and subjected to a chemical composition treatment to obtain a low-temperature lithium battery, including a shell 1, a battery cell 2, and an electrolyte 3. The inner wall of the shell 1 is provided with a battery cell 2, and the inner wall of the shell 1 is filled with the electrolyte 3.

[0062] The capacity of the low-temperature lithium batteries prepared in Examples 1 to 5 is increased by 20% to 35%.

[0063] Comparative experiment:

[0064] The difference between Comparative Example 1 and Example 1 is that;

[0065] The positive electrode material includes the following parts by weight of material A, 5 parts of graphene, 5 parts of carbon nanotubes, and 220 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following weight parts of binder polyvinylidene fluoride 90 parts, conductive agent SP 10 parts, and solvent NMP 6 parts are added to the composite lithium iron phosphate positive electrode material, and stirred to obtain lithium iron phosphate positive electrode material slurry. The mass ratio of the composite lithium iron phosphate positive electrode material, the conductive agent SP, and the binder polyvinylidene fluoride PVDF is 95-100:2-3:1-4, and the slurry viscosity is adjusted by adding the solvent NMP so that the viscosity of the lithium iron phosphate positive electrode material slurry reaches 8050-15050 mPa.s.

[0066] The difference between Comparative Example 1 and Example 2 is that;

[0067] The positive electrode material includes the following parts by weight of material A, 10 parts of graphene, 10 parts of carbon nanotubes, and 280 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following weight parts of binder polyvinylidene fluoride 100 parts, conductive agent SP 12 parts, and solvent NMP 6 parts are added to the composite lithium iron phosphate positive electrode material, and stirred to obtain lithium iron phosphate positive electrode material slurry. The mass ratio of the composite lithium iron phosphate positive electrode material, the conductive agent SP, and the binder polyvinylidene fluoride PVDF is 95-100:2-3:1-4, and the slurry viscosity is adjusted by adding the solvent NMP so that the viscosity of the lithium iron phosphate positive electrode material slurry reaches 8050-15050 mPa.s.

[0068] The difference between Comparative Example 1 and Example 3 is that;

[0069] The positive electrode material includes the following parts by weight of material A, 25 parts of graphene, 15 parts of carbon nanotubes, and 250 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following weight parts of binder polyvinylidene fluoride 115 parts, conductive agent SP 13 parts, and solvent NMP 7 parts are added to the composite lithium iron phosphate positive electrode material, and stirred to obtain lithium iron phosphate positive electrode material slurry. The mass ratio of the composite lithium iron phosphate positive electrode material, the conductive agent SP, and the binder polyvinylidene fluoride PVDF is 95-100:2-3:1-4, and the slurry viscosity is adjusted by adding the solvent NMP so that the viscosity of the lithium iron phosphate positive electrode material slurry reaches 8050-15050 mPa.s.

[0070] The difference between Comparative Example 1 and Example 4 is that;

[0071] The positive electrode material includes the following parts by weight of material A, 35 parts of graphene, 25 parts of carbon nanotubes, and 290 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-sized particles of 50140nm. , add the following weight parts of binder polyvinylidene fluoride 90 parts, conductive agent SP 13 parts, solvent NMP 8 parts to the composite lithium iron phosphate positive electrode material, stir to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of the composite lithium iron phosphate positive electrode material, conductive agent SP, and binder polyvinylidene fluoride PVDF is 95-100:2-3:1-4, and the slurry viscosity is adjusted by adding solvent NMP to make the viscosity of the lithium iron phosphate positive electrode material slurry reach 8050-15050mPa.s.

[0072] The difference between Comparative Example 1 and Example 5 is that;

[0073] The positive electrode material includes the following parts by weight of material A, 26 parts of graphene, 32 parts of carbon nanotubes, and 290 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1% to 5%, 0.1% to 5%, and 96% to 99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following weight parts of binder polyvinylidene fluoride 112 parts, conductive agent SP 14 parts, and solvent NMP 12 parts are added to the composite lithium iron phosphate positive electrode material, and stirred to obtain lithium iron phosphate positive electrode material slurry. The mass ratio of the composite lithium iron phosphate positive electrode material, the conductive agent SP, and the binder polyvinylidene fluoride PVDF is 95-100:2-3:1-4, and the slurry viscosity is adjusted by adding the solvent NMP so that the viscosity of the lithium iron phosphate positive electrode material slurry reaches 8050-15050 mPa.s.

[0074] The low-temperature lithium batteries of Examples 1, 2, 3, 4, and 5 of the present invention and the conventional low-temperature lithium battery (Comparative Example 1) were subjected to freeze resistance tests and stability rate tests, respectively, and their protection values ​​were calculated and statistically analyzed, and the results are shown in Table 1.

[0075] Resistance Frost resistance rate (%) Stability rate (%) Example 1 98 98 Example 2 97 g6 Example 3 98 95 Example 4 g6 97 Example 5 96 98 Comparative Example 1 85 80

[0076] From the data in Table 1, it can be seen that the freezing resistance rates of the low-temperature lithium batteries in Examples 1, 2, 3, 4 and 5 of the present invention are 98, 97, 98, 96 and 96 respectively, which are significantly higher than the freezing resistance rate of the low-temperature lithium battery in Comparative Example 1. This indicates that the freezing resistance rate of the low-temperature lithium battery of the present invention is significantly improved, which improves its applicability for use in cold environments.

[0077] From the data in Table 1, it can be seen that the stability rates of the low-temperature lithium batteries in Examples 1, 2, 3, 4 and 5 of the present invention are 98, 96, 95, 97 and 98 respectively, which are significantly higher than the stability rate of the low-temperature lithium battery in Comparative Example 1. This indicates that the stability rate of the low-temperature lithium battery of the present invention is significantly improved, which improves the stability of use in cold environments.

[0078] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a low-temperature lithium battery with large capacity and high safety, characterized in that: The steps include: Step S1, preparing positive electrode material; Step S2, preparing negative electrode materials; Step S3, preparation of pole piece; Step S4, assembling the battery cells (2) into a lithium battery; The positive electrode material comprises the following parts by weight of material A, 2-40 parts of graphene, 2-40 parts of carbon nanotubes, and 200-300 parts of nano lithium iron phosphate. Material A is dry-mixed by an organic silicon coupling agent to obtain a composite lithium iron phosphate positive electrode material. The mass percentages of graphene, carbon nanotubes, and nano lithium iron phosphate in the composite lithium iron phosphate positive electrode material are 0.1%-5%, 0.1%-5%, and 96%-99%, respectively. The primary particles of nano lithium iron phosphate are nano-scale grains of 50140nm. The following parts by weight of binder polyvinylidene fluoride are added to the composite lithium iron phosphate positive electrode material: 80-110 parts, 8-15 parts of conductive agent SP, 4-15 parts of solvent NMP, stirring to obtain lithium iron phosphate positive electrode material slurry, the mass ratio of composite lithium iron phosphate positive electrode material, conductive agent SP, and binder polyvinylidene fluoride PVDF is 95-100:2-3:1-4, and the viscosity of the slurry is adjusted by adding solvent NMP to make the viscosity of the lithium iron phosphate positive electrode material slurry reach 8050-15050mPa.s, the solid content is 50%, and the lithium iron phosphate positive electrode material slurry is coated after sieving, and the double-sided coating surface density of the positive electrode sheet is 150-300g / cm 2 , one of the elements Mn, Al, Cr, Mg, and F is added to the positive electrode material slurry to perform bulk doping on the positive electrode material and increase the interlayer spacing of the material.

2. The method for preparing a large-capacity, high-safety, low-temperature lithium battery according to claim 1, characterized in that: The negative electrode material comprises the following parts by weight of hard carbon negative electrode material 15-40 parts, sodium carboxymethyl cellulose 20-60 parts, styrene-butadiene rubber 25-45 parts, and water 40-60 parts, which are evenly mixed to form material B. The porosity of the hard carbon negative electrode material is 3%-10%. The mass ratio of the hard carbon material, sodium carboxymethyl cellulose, and styrene-butadiene rubber is 96-125:2-5:2-5. Material B is glued into a negative electrode slurry with a solid content of 55-60%. The negative electrode slurry is coated, and the double-sided coating surface density of the negative electrode sheet is 60-120 g / cm2. One of the elements B and K is introduced into the negative electrode slurry to improve the graphite structure and increase the interlayer spacing.

3. The method for preparing a low-temperature lithium battery with large capacity and high safety according to claim 2, characterized in that: The CA ratio of the negative electrode sheet to the positive electrode sheet is 1.05-1.

20. The coated positive electrode sheet and negative electrode sheet are dried, rolled, cut, and the tabs are welded. Both the positive and negative electrode tabs are full tabs.

4. The method for preparing a low-temperature lithium battery with large capacity and high safety according to claim 1, characterized in that: 10 to 15 parts by weight of N-methylpyrrolidone is added to the positive electrode material slurry, and the mixture is stirred to form a uniform positive electrode material slurry.

5. The method for preparing a low-temperature lithium battery with large capacity and high safety according to claim 2, characterized in that: 12 to 18 parts by weight of styrene-butadiene rubber is added to the negative electrode slurry, and the styrene-butadiene rubber can improve the stability and safety of the negative electrode structure.

6. The method for preparing a low-temperature lithium battery with large capacity and high safety according to claim 2, characterized in that: A separator is provided between the positive electrode plate and the negative electrode plate, and the separator is one of polyethylene and polypropylene.

7. The method for preparing a low-temperature lithium battery with large capacity and high safety according to claim 6, characterized in that: The positive electrode sheet, the negative electrode sheet and the separator are wound to form a battery core (2), the battery core (2) is placed in a housing (1) and an electrolyte (3) is injected, the battery core (2) is sealed, and a chemical and capacity processing is performed to obtain a low-temperature lithium battery.

8. A low-temperature lithium battery with large capacity and high safety, suitable for the preparation method of a low-temperature lithium battery with large capacity and high safety as claimed in any one of claims 1 to 7, characterized in that: It comprises a shell (1), a battery core (2), and an electrolyte (3); the battery core (2) is installed on the inner wall of the shell (1), and the electrolyte (3) is filled on the inner wall of the shell (1).

Citation Information

Patent Citations

  • Low-temperature improved lithium titanate battery and preparation method thereof

    CN109119699A

  • Low-temperature lithium iron phosphate battery and preparation method thereof

    CN109802094A

  • A low-temperature electrode sheet, its preparation method, and a low-temperature lithium battery

    CN111816882B

  • A kind of electrolyte for low temperature lithium battery and preparation method thereof

    CN113594544B

  • Novel ultralow temperature lithium ion battery, and preparation method thereof

    CN108493405A